Analisis Alokasi Tenaga Kerja Pada Proyek Pembangunan Gedung Sekolah Di Jalan Kecipir - Arum Chofifah Nuranisa; Almuntofa Purwantoro (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2024)
The rapid development of construction projects and population growth in Indonesia creates a great need for facility development. A project is a method that combines a series of temporary activities with a starting and ending point. In construction service companies, a common problem that often occurs is human resource management. Human resource planning methods that are not optimal and their allocation is uneven can hamper project completion. This article aims to analyze the allocation of labor, especially in the school construction project on Jalan Kecipir. The research was carried out for 3 three months, from December 2023 – February 2024. The required data was collected by conducting literature studies and requesting data from related parties. The data analysis technique used is the Resource Leveling method using Microsoft Project Software. The results show that the allocation of labor in the school building construction project on Jalan Kecipir is uneven and experiencing overall allocation (excess allocation). There are several types of workers whose labor requirements exceed the limit of labor availability, including workers, foremen, bricklayers, head carpenters, carpenters and ironworkers. With the highest demand for each workforce, there are 54 workers, 12 foremen, 18 bricklayers, 6 head carpenters, 20 carpenters and 15 ironworkers